Hard wheat compared to soft wheat for finishing swine - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three feeding trials were conducted to compare soft winter wheat with hard winter wheat for finishing swine. In each trial, soft wheat diets supported weight gains and feed/gain ratio equal to those observed for pigs fed hard winter wheat diets. Both soft and hard wheat diets were compared with milo basal diets resulting in similar performances and reaffirming that wheat can replace all the milo in a swine diet. The study involving the method of processing the wheat diets indicated that rolled wheat diets resulted in pig performance superior to ground diets. Pelleting wheat diets was superior to both grinding and rolling as shown by performance. Soft wheat as well as hard wheat can be fed to finishing swine with only the addition of lysine. No soybean meal is needed since lysine is the only limiting amino acid in wheat-based finishing diets.
Keywords: Swine; Hard wheat vs. soft wheat; Finishing pigs